2007
DOI: 10.1529/biophysj.106.099945
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Lateral Segregation Driven by Diacyl Cyclodextrin Interactions at the Membrane Surface

Abstract: Cyclodextrins are hydrophilic molecular cages with a hydrophobic interior allowing the inclusion of water-insoluble drugs. Amphiphilic cyclodextrins obtained by appending a hydrophobic anchor were designed to improve the cell targeting of the drug-containing cavities through their liposome transportation in the organism. After insertion in model membranes, they were found to induce a lateral phase separation into a pure lipid phase and a fluid cyclodextrin-rich phase (L(CD)) with reduced acyl chain order param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 42 publications
7
34
0
Order By: Relevance
“…In subsequent advancements aiming to overcome certain difficulties encountered with phospholipidyl-cyclodextrins, namely high cost, tedious synthesis and rather poor chemical stability, a new class of amphiphilic cyclodextrins was designed [20] and referred to as the peptidolipidyl-cyclodextrins. Compared to phospholipidyl-cyclodextrins, the peptidolipidyl-cyclodextrins differ in that the chiral glycero-phosphate moiety is replaced by an amino-acid group providing the following advantages:…”
Section: Introductionmentioning
confidence: 99%
“…In subsequent advancements aiming to overcome certain difficulties encountered with phospholipidyl-cyclodextrins, namely high cost, tedious synthesis and rather poor chemical stability, a new class of amphiphilic cyclodextrins was designed [20] and referred to as the peptidolipidyl-cyclodextrins. Compared to phospholipidyl-cyclodextrins, the peptidolipidyl-cyclodextrins differ in that the chiral glycero-phosphate moiety is replaced by an amino-acid group providing the following advantages:…”
Section: Introductionmentioning
confidence: 99%
“…Di- and polysubstituted amphiphilic cyclodextrins have been obtained by grafting of aliphatic chains or cholesteryl moieties on the primary hydroxyl groups of the cyclodextrin rim via amine, sulphur or sulfoxide linkers [ 13 , 14 , 15 , 16 , 53 , 54 ]. Studies of the interfacial properties of these compounds have shown that they may form stable monomolecular layers at the air-water interface [ 13 , 14 , 15 , 16 ].…”
Section: Amphiphilic Cyclodextrinsmentioning
confidence: 99%
“…The fact that modified cyclodextrins can be mixed in various proportions with phospholipids, cholesterol, and other amphiphilic molecules has been exploited for preparation of functionalized lipid membranes and organized biomimetic systems ( Table 2 ). Hydrated mixtures of lipids and amphiphilic cyclodextrins may spontaneously assemble into unilamellar spherical vesicles ( Figure 7 a), giant unilamellar vesicles ( Figure 7 b) or multilamellar liposomes [ 28 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. More sophisticated hybrid structures, involving cyclodextrin derivatives, have been prepared by controlled deposition techniques employing nanoarchitectonics means [ 7 , 14 , 15 ].…”
Section: Nanosystems Of Amphiphilic Cyclodextrins Mixed With Membrmentioning
confidence: 99%
See 2 more Smart Citations